2015
DOI: 10.1017/jrr.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

School Counsellors’ and Students’ Attitudes to Online Counselling: A Qualitative Study

Abstract: An exploratory qualitative study was conducted to examine the perceptions and attitudes of both school counsellors and students to online counselling. Focus groups were conducted with two groups of school counsellors and six groups of secondary students. It was found that counsellors were hesitant to use online counselling because they were not convinced that it was effective, and without the necessary online skills, they were concerned they would not be competent to deal with potential litigious and security … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…Demand on e-counseling from students reflected that students were keener to seek counselling help online than face-to-face counselling due to stigma issues (Fang et al, 2017;Zainudin & Yusop, 2018). Studies had reported that many young people with issues would not approach for help if online help were not made available to them (Dowling & Rickwood, 2014; Glasheen & Campbell, 2009;Glasheen et al, 2015). Therefore, e-counseling provides a platform for anonymity and a safe environment that allows more students to be connected, reached and counselled (Bambling et al, 2008;Harrad & Banks, 2016;Hanley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Demand on e-counseling from students reflected that students were keener to seek counselling help online than face-to-face counselling due to stigma issues (Fang et al, 2017;Zainudin & Yusop, 2018). Studies had reported that many young people with issues would not approach for help if online help were not made available to them (Dowling & Rickwood, 2014; Glasheen & Campbell, 2009;Glasheen et al, 2015). Therefore, e-counseling provides a platform for anonymity and a safe environment that allows more students to be connected, reached and counselled (Bambling et al, 2008;Harrad & Banks, 2016;Hanley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Web-based mental health resources, also known as e-mental health, may overcome many of the challenges faced by school counselors [ 35 ]. Young people are very willing to seek help for mental health via the Internet [ 36 , 37 ], and Web resources provide convenient access to information and support. However, school counselors have been found to be reluctant to use some types of Web resources, specifically online counseling [ 36 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Young people are very willing to seek help for mental health via the Internet [ 36 , 37 ], and Web resources provide convenient access to information and support. However, school counselors have been found to be reluctant to use some types of Web resources, specifically online counseling [ 36 , 38 ]. Lack of training, misbeliefs about quality and efficacy, confidentiality, and dishonesty concerns have been found to affect the use of online counseling in school settings [ 36 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of EBPs may indirectly lower burnout by increasing school counsellors’ capacity to reach students (Glasheen, Campbell, & Shochet, 2015). Burnout may also be reduced by the use of internet-based resources for mental health (e.g., psychoeducation websites, mobile phone apps, or online counselling), as school counsellors can use these to improve students’ mental health literacy, provide care beyond school hours, and increase engagement with care (Glasheen et al, 2015). However, little is known about school counsellors’ use of EBPs or online therapies and the relationship with burnout.…”
mentioning
confidence: 99%